2016
DOI: 10.1353/eca.2016.0014
|View full text |Cite
|
Sign up to set email alerts
|

Does the United States Have a Productivity Slowdown or a Measurement Problem?

Abstract: After 2004, measured growth in labor productivity and total factor productivity slowed. We find little evidence that this slowdown arises from growing mismeasurement of the gains from innovation in information technology-related goods and services. First, the mismeasurement of information technology hardware is significant preceding the slowdown. Because the domestic production of these products has fallen, the quantitative effect on productivity was larger in the 1995-2004 period than since then, despite mism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
146
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(160 citation statements)
references
References 31 publications
(63 reference statements)
10
146
0
4
Order By: Relevance
“…5 As discussed in Byrne, Fernald, and Reinsdorf (2016), ICT price mismeasurement has been with us for some time, and mismeasurement can only explain a small portion of the "missing output" from the productivity slowdown (see also Syverson 2016). The ICT equipment prices described in and used in this paper were used in Byrne et al (2016), who concluded that mismeasurement of ICT prices cannot explain the recent slowdown in output per hour.…”
Section: Ict Prices and Ict Servicesmentioning
confidence: 84%
See 1 more Smart Citation
“…5 As discussed in Byrne, Fernald, and Reinsdorf (2016), ICT price mismeasurement has been with us for some time, and mismeasurement can only explain a small portion of the "missing output" from the productivity slowdown (see also Syverson 2016). The ICT equipment prices described in and used in this paper were used in Byrne et al (2016), who concluded that mismeasurement of ICT prices cannot explain the recent slowdown in output per hour.…”
Section: Ict Prices and Ict Servicesmentioning
confidence: 84%
“…The ICT equipment prices described in and used in this paper were used in Byrne et al (2016), who concluded that mismeasurement of ICT prices cannot explain the recent slowdown in output per hour.…”
Section: Ict Prices and Ict Servicesmentioning
confidence: 99%
“…These analyses highlight the roles of slowing labor force growth due to demographics and a slowdown in trend productivity growth. The productivity slowdown in the United States is documented by Byrne et al (2016) and Gordon (2016), and the European productivity slowdown is analyzed in Cette et al (2016).…”
Section: Estimates Of the Output Gap And Trend Gdp Growthmentioning
confidence: 99%
“…Much of that surge reflected gains in hardware production, in part because competition within the semiconductor industry led to the faster introduction of new chips. In the 2000s, the pace of TFP gains in ICT production eased and its share in GDP declined (see Byrne, Fernald, and Reinsdorf, 2016).Hence, the direct contribution of ICT-producing industries fell.In the early 2000s, the contribution of market services industries especially bulged. We define this group as wholesale and retail trade, transportation, information, and business services.…”
mentioning
confidence: 99%